An optimal design method for low-impact development (LID) facilities based on the hydrodynamic model and genetic algorithm-assisted decision-making - Zhang, Wenqing; Hou, Jingming; Shen, Tengfei; Zhang, Ye; Li, Donglai; Wang, Jian; Zhang, Jianqi (Water policy, 2023)
The construction of low-impact development (LID) facilities has become an effective means to control urban waterlogging, but there is still a lack of scientific methods to achieve its accurate and reasonable planning and design. In this work, a high-precision hydrodynamic model was used to evaluate the construction effect of each LID facility scheme, and the fitted functional relationship was used to describe the law between the LID facility construction area and the construction effect. Finally, a genetic algorithm was used to automatically optimize the best LID facility construction scheme. Applying this method to the actual urban LID facility planning and construction, the optimal solution law is that the construction effect of single and combined LID facilities increases with the increase of construction cost. In the same low-cost construction scheme, the construction effect of combined LID facilities will be lower than that of single LID facilities, but with the continuous increase of construction cost, the construction effect of combined LID facilities will eventually be better than that of single LID facilities. According to this method, the decision-maker can get the optimal LID facility construction scheme to meet the actual engineering needs